CRITICAL THINKING ROLE IN EDUCATIONAL REFORM OF HIGH SCHOOL IN INFORMATION SOCIETY - Денисевич, О. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article information society special features has been considered like influence on the educational paradigm of higher school, critical thinking has been analyzed like effective instrument of education process.